The Public Value of e-Government from the Perspective of Private-Sector Professionals in Morocco - Idaomar Chaimaa; Chafik Khalid (European Scientific Journal, ESJ, 2023)
This research aims to assess the public value of e-government in Morocco, using Delone and Mclean's (2016) Information Systems (IS) success model as a reference framework. The methodology is based on a qualitative exploratory study involving 13 companies, including law firms, architecture firms and real estate developers firms. An interview guide was designed to collect data, which were analyzed using Nvivo Qsr 12 software. The analysis identified six variables, namely "Human Capital, Telecommunication Infrastructure, Willingness to Use, State Strategy, Continuous Education, and Culture," which were added to the seven predetermined variables of the Delone and Mclean (2016) IS Success Model. The results of this study conclude the need for public organizations, especially the government, to direct their investments toward human capital and telecommunication infrastructure. This aligns with carefully planned strategies for digitizing public services, aiming to strengthen essential values such as trust, transparency, fairness, time efficiency, and cost reduction.